(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The previously studies of enzymes were focused only on the extraction and purification of enzyme and increase the toxic effect of drugs and supplement of free radical scavenging. So, the aim of the study was to extend purified peroxidase from Pseudomonas aeruginosa application and to abundant new enzymatic drug of free radicals scavenging with low side effect. Peroxidase is categorized as oxido-reductases, which were used for catalyzing various oxidative reactions that protect cells from the harm effect of free radicals .Peroxidase was tested as antioxidant and test their toxicity on human cells to overcome the problem of the side effect of drug and supplement that used as an antioxidant. The enzyme was applied as H2O2 scavenging activity antioxidant by used three concentration of enzyme and triplicate (10, 40, 60 µg/ml). The enzyme was show higher activity at 60 µg/ml reached to 40% activity. The cytotoxicity of peroxidase was tested on whole healthy human blood by C.B.C by using equal amount 5µg of (enzyme substrate, only substrate and enzyme without substrate). The result showed that the enzyme only had no effect on human blood as compare with H2O2 and enzyme with H2O2. The characterization of enzyme was done by using more than one temperature and pH value and the result were shown that the optimal temperature for enzyme activity and stability rang (40-45°C) and the optimal pH for enzyme stability and activity were 7.